2015
DOI: 10.1111/jmft.12120
|View full text |Cite
|
Sign up to set email alerts
|

The Gap Between Couple Therapy Research Efficacy and Practice Effectiveness

Abstract: Meta‐analyses of randomized controlled trials of couple therapy find large improvements in couple adjustment, but published evaluations of the effectiveness of couple therapy in routine practice find only small‐to‐moderate effects. The current study analyzes possible explanations for the research‐efficacy to practice‐effectiveness gap and offers suggestions for enhancing couple therapy effectiveness. Major recommendations are that therapists should clarify whether couples’ therapy goal is to clarify commitment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
63
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 101 publications
9
63
0
2
Order By: Relevance
“…These findings, in conjunction with other effectiveness studies of couple therapy (Halford et al, 2015), suggest that there is a gap between the effects seen in clinical trials and those realized in day-to-day practice. Couple therapy as practiced in the community appears to have some beneficial effects, especially in preventing (or stopping) declines in relationship quality.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…These findings, in conjunction with other effectiveness studies of couple therapy (Halford et al, 2015), suggest that there is a gap between the effects seen in clinical trials and those realized in day-to-day practice. Couple therapy as practiced in the community appears to have some beneficial effects, especially in preventing (or stopping) declines in relationship quality.…”
Section: Discussionsupporting
confidence: 59%
“…Although the findings from efficacy studies are noteworthy, several researchers and theorists have raised concerns about the gap between research on couple therapies and what is used in practice (e.g., Gurman, 2011;Halford, Pepping, & Petch, 2015). Several studies on treatment-as-usual couple therapy have demonstrated that treatment gains are about a half to a third as compared to couple treatments in efficacy studies (e.g., Anker, Duncan, & Sparks, 2009;Doss et al, 2012;Hahlweg & Klann, 1997;Klann, Halweg, Baucom, & Kroeger, 2011;Lunblad & Hansson, 2006).…”
mentioning
confidence: 99%
“…Although it was not the primary focus of treatment, the findings indicated that there was only a modest improvement for clients overall in relationship satisfaction and no meaningful change for nonclient partners as a group; within-group effect sizes were 0.43 and 0.21 for clients and nonclient partners, respectively, compared to the average effect size of 0.6 in effectiveness studies for treating relationship distress as reported by Halford et al (2016). However, in an effectiveness study of Integrative Behavioral Couple Therapy (IBCT) for relationship discord currently being conducted in the Veterans Administration (Christensen & Doss, 2017) and perhaps more similar to this study (i.e., approximately 10 sessions on average with high rates of comorbid psychiatric diagnoses), Christensen (2017) reports effect sizes for relationship satisfaction ranging from 0.21 to 0.57, similar to the current effect sizes.…”
Section: Discussionmentioning
confidence: 79%
“…At present, there are no studies involving treating depression with a couple-based intervention in routine clinical settings (i.e., effectiveness research), and comparable effects to efficacy outcomes cannot be assumed. For example, Halford, Pepping, and Petch (2016) showed that the rate of couple recovery from relationship distress in clinical effectiveness trials was less than half of that reported in efficacy trials. Similarly, when comparing efficacy and effectiveness trials for individual or group CBT for depression (no partner involvement), Hans and Hiller (2013) concluded that CBT 1 For a history of the development of IAPT and how it has been implemented and evaluated, see Clark (2011).…”
mentioning
confidence: 99%
“…The idea of limiting clinical practice to treatments with experimental evidence of positive effects (i.e., evidence‐based practice) has given rise to a counter movement toward broadening of the concept of evidence, in order to consider knowledge derived from real practice (e.g., Gordon, Pell, & Pell, ; Halford et al., ). A strategy for gathering practice‐based evidence of the real effects of talking therapies consists of evaluating outcomes in each and every patient, and using technological platforms for treating and archiving the large scale resulting databases.…”
mentioning
confidence: 99%